ANALYSIS OF FLUCTUATIONS IN TOTAL ORGANIC MATTER (TOM) AND N/P RATIO ON THE GROWTH OF VANAME SHRIMP (LITOPENAEUS VANNAMEI) - Nindarwi, Daruti Dinda; Agustin, Ayu Rizky; Dewi , Nina Nurmalia (Universitas Mataram, 2025)
Whiteleg shrimp are superior in aquaculture due to their high survival rates in intensive cultivation systems, but the use of artificial feed increases aquatic organic matter, reducing dissolved oxygen and causing ecosystem instability. This oxygen depletion affects the survival, growth, and average daily growth (ADG) of the shrimp. Therefore, this study will present data on the correlation between Total Organic Matter (TOM) and the N/P ratio as the end product of the decomposition of organic matter on ADG vaname shrimp body weight gain from intensive shrimp ponds in Banyuwangi, East Java. Data sampling was carried out in 11 intensive rearing ponds at the age of 20 – 60 days of shrimp culture. Data correlation will be analyzed by correlation test using SPSS. The TOM obtained was in the range of 60.67 – 69.52 mg/l. The N/P ratio value obtained is 1.25 – 25.33. The ADG value obtained is 0.15 – 0.59 grams/day. The correlation between TOM and ADG shows a correlation coefficient of 0.468 which states that there is a positive correlation with a moderate level of correlation. The correlation between the N/P ratio and ADG shows a correlation coefficient of 0.066 which states that the results are negative or there is no correlation.